Psychophysiologic symptom relief therapy for chronic back pain: a pilot randomized controlled trial. (23rd September 2021) - Donnino, Michael W.; Thompson, Garrett S.; Mehta, Shivani; Paschali, Myrella; Howard, Patricia; Antonsen, Sofie B.; Balaji, Lakshman; Bertisch, Suzanne M.; Edwards, Robert; Ngo, Long H.; Grossestreuer, Anne V.
Abstract : Supplemental Digital Content is Available in the Text. A pilot study assessing whether psychophysiologic symptom relief therapy can reduce nonspecific back pain compared with usual care and mindfulness-based stress reduction. Abstract: Introduction: Chronic back pain is the leading cause of disability in the United States. Based on the hypothesis that nonspecific back pain may be rooted in a psychophysiologic etiology, we propose a new approach to chronic back pain. Objectives: A pilot study was conducted to assess whether psychophysiologic symptom relief therapy (PSRT) can reduce disability and back pain bothersomeness for patients with chronic back pain. Methods: This was a three-armed, randomized trial for adults with nonspecific chronic back pain that compared PSRT with usual care and an active comparator (mindfulness-based stress reduction [MBSR]). Psychophysiologic symptom relief therapy–randomized participants received a 12-week (36 hours) course based on the psychophysiological model of pain. All groups were administered validated questionnaires at baseline and at 4, 8, 13, and 26 weeks. The primary outcome was the reduction in pain disability measured by the Roland–Morris Disability Questionnaire. Results: The mean Roland–Morris Disability Questionnaire score for the PSRT group (n = 11) decreased from 9.5 (±4.3 SDs) to 3.3 (±5.1) after 26 weeks which was statistically significant compared with both MBSR (n = 12) ( P = 0.04) and usual care (n = 12) ( P = 0.03). Pain bothersomeness scores and pain-related anxiety decreased significantly over 26 weeks in PSRT compared with MBSR and usual care (data in manuscript). At 26 weeks, 63.6% of the PSRT arm reported being pain free (0/10 pain) compared with 25.0% and 16.7% in MBSR and usual care arms, respectively. Psychophysiologic symptom relief therapy attendance was 76%, and there was 100% follow-up of all groups. Conclusion: Psychophysiologic symptom relief therapy is a feasible and potentially highly beneficial treatment for patients with nonspecific back pain.